2007
DOI: 10.1080/10407780701364536
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Quadrature Solution of Natural Convection in an Enclosure with a Partial Partition

Abstract: Natural convection in a partially divided enclosure has been examined numerically using a differential quadrature method. Governing equations for the flow and heat transfer have been constructed by the vorticity-stream function formulation and computational results have been obtained for the Rayleigh numbers, 10 4 , 10 5 , 10 6 , the locations of the partition, 0.2, 0.4, 0.6, 0.8, and the partition ratios, 0.25, 0.50, 0.75, 1.0. The results show that circulation strength, and therefore heat transfer, decreases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…They concluded that the introduction of a complete vertical partition reduces convective heat transfer from 59.1% to 63.6% in the range of Rayleigh numbers 38, 000 < Ra < 369, 000. [6] reported the average Nusselt number increases with decreasing of thermal resistance of the partition and the partition thickness has little effect on heat transfer. [7] studied a vertically divided square enclosure by a solid partition into air and water regions and found that filling of fluid into chests is important for obtaining maximum heat transfer and energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the introduction of a complete vertical partition reduces convective heat transfer from 59.1% to 63.6% in the range of Rayleigh numbers 38, 000 < Ra < 369, 000. [6] reported the average Nusselt number increases with decreasing of thermal resistance of the partition and the partition thickness has little effect on heat transfer. [7] studied a vertically divided square enclosure by a solid partition into air and water regions and found that filling of fluid into chests is important for obtaining maximum heat transfer and energy saving.…”
Section: Introductionmentioning
confidence: 99%
“…DQM is an effective computational method and rapid convergence solution for nonlinear problems. The mentioned method has a wide range of mechanical, civil and aerospace engineering applications due to its potential for solving nonlinear partial differential equations (Gorji et al, 2017; Kalayci Sahinoglu and Ozer, 2020; Malekzadeh et al, 2006; Nowamooz et al, 2015; Öztuna, 2007; Tornabene et al, 2015; Trinh et al, 2021; Wang et al, 2021). The DQM approximates the derivative of a function at each grid point as a weighted linear summation of the function values in the whole discrete domain.…”
Section: Introductionmentioning
confidence: 99%